The Trans-Neptunian Solar System 2020
DOI: 10.1016/b978-0-12-816490-7.00016-3
|View full text |Cite
|
Sign up to set email alerts
|

Extrasolar Kuiper belts

Abstract: Extrasolar debris disks are the dust disks found around nearby main sequence stars arising from the break-up of asteroids and comets orbiting the stars. Far-IR surveys (e.g., with Herschel) showed that ∼ 20% of stars host detectable dust levels. While dust temperatures suggest a location at 10s of au comparable with our Kuiper belt, orders of magnitude more dust is required implying a planetesimal population more comparable with the primordial Kuiper belt. High resolution imaging (e.g., with ALMA) has mapped t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 143 publications
(160 reference statements)
1
14
0
Order By: Relevance
“…9). The EF-related banded structure, or enhancements outside the various "snow lines" in general, as well as significant radial dips in the metallicity seen in our models, may provide an explanation for ALMA observations that show well defined particle belts at large radii (Carrasco-González et al 2019;Segura-Cox et al 2020), or for the formation of "ExoKuiper belts" seen in revealed systems (Wyatt 2020).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…9). The EF-related banded structure, or enhancements outside the various "snow lines" in general, as well as significant radial dips in the metallicity seen in our models, may provide an explanation for ALMA observations that show well defined particle belts at large radii (Carrasco-González et al 2019;Segura-Cox et al 2020), or for the formation of "ExoKuiper belts" seen in revealed systems (Wyatt 2020).…”
Section: Discussionsupporting
confidence: 50%
“…Perhaps most striking is that most of the mass in the lowest α t model is in the vapor phase and close to the star, suggesting that this vast reservoir could eventually contribute to these bands as the disk cools and the vapor recondenses. Planetesimals that may form within these bands at an early time are resistant to inward migration as the EF itself evolves inwards, this may give rise to debris belts -"fossils" of a previous radial location of the EF -that may constantly produce pebbles and visible dust via collisions which may be reaccreted or drift inwards, as seen in the so-called "Exo-Kuiper Belts" seen in exoplanetary systems (Wyatt 2020).…”
Section: Bulk Planetesimal Compositionmentioning
confidence: 99%
“…Recall that most condensable material mass is in the vapor phase closer to the Sun for the lowest α t models (see Figure 9). The EF-related banded structure, or enhancements outside the various "snowlines" in general, as well as significant radial dips in the metallicity seen in our models, may provide an explanation for ALMA observations that show well-defined particle belts at large radii (Carrasco-González et al 2019;Segura-Cox et al 2020), or for the formation of "Exo-Kuiper Belts" seen in revealed systems (Wyatt 2020).…”
Section: Discussionmentioning
confidence: 50%
“…3B. Given the expected variation in 26 Al content from system to system, it is interesting to look at extra-solar Kuiper Belts (Wyatt 2020), as it is now becoming possible to constrain the volatile content of planetesimals at 10s to 100s of au in a handful of systems (e.g., Marino et al 2016;Kral et al 2017). Constraints on the (CO+CO 2 ) mass content of planetesimals range from <1 to ≈35% (Wyatt 2020), broadly consistent with the ranges we find in e.g., Figs.…”
Section: Debris Disks and Kuiper Belt Analogsmentioning
confidence: 99%